2017
DOI: 10.4049/jimmunol.1700822
|View full text |Cite
|
Sign up to set email alerts
|

Transient BAFF Blockade Inhibits Type 1 Diabetes Development in Nonobese Diabetic Mice by Enriching Immunoregulatory B Lymphocytes Sensitive to Deletion by Anti-CD20 Cotherapy

Abstract: In NOD mice and also likely humans, B-lymphocytes play an important role as APC expanding autoreactive T-cell responses ultimately causing type 1 diabetes (T1D). Currently, humans at high future T1D risk can only be identified at late prodromal stages of disease indicated by markers such as insulin autoantibodies (IAA). When commenced in already IAA+ NOD mice, continuous BAFFR-Fc treatment alone or in combination with anti-CD20 (designated combo therapy) inhibited T1D development. Despite eliciting broader B-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…In myasthenia gravis, depletion of B cells with RTX showed that IL-10 + B cells can be found to have repopulated in the periphery after several months ( 219 ). Immunosuppressive treatments, TNF-therapy, and BAFF-blockade in RA ( 206 ), SSc ( 213 ), and experimental diabetes mellitus type 1 ( 220 ), respectively, have shown that IL-10-producing B lineage cells enrich after treatment and that their frequency is even higher than before treatment. In relapsing-remitting MS, the frequencies of IL-10 + CD19 + B cells were significantly reduced in patients experiencing a relapse compared with that in patients in remission ( 217 ), indicating that the clinical outcome of the disease also depends on the availability of IL-10-producing B cells.…”
Section: Induction Of Anti-inflammatory B Lineage Cells: a Promising mentioning
confidence: 99%
“…In myasthenia gravis, depletion of B cells with RTX showed that IL-10 + B cells can be found to have repopulated in the periphery after several months ( 219 ). Immunosuppressive treatments, TNF-therapy, and BAFF-blockade in RA ( 206 ), SSc ( 213 ), and experimental diabetes mellitus type 1 ( 220 ), respectively, have shown that IL-10-producing B lineage cells enrich after treatment and that their frequency is even higher than before treatment. In relapsing-remitting MS, the frequencies of IL-10 + CD19 + B cells were significantly reduced in patients experiencing a relapse compared with that in patients in remission ( 217 ), indicating that the clinical outcome of the disease also depends on the availability of IL-10-producing B cells.…”
Section: Induction Of Anti-inflammatory B Lineage Cells: a Promising mentioning
confidence: 99%
“…For example, an intriguing new study showed that TACI-dependent production of the regulatory cytokine IL-10 by IgA + plasma cells protected against experimental autoimmune encephalomyelitis (EAE) in BAFF-Tg mice. 144,145 Finally, multiple mouse studies have demonstrated decreased renal inflammation in BAFF-deficient and BAFF-R-Ig/TACI-Igtreated lupus models in excess of impacts on serum autoantibody titers. 139 Together, these mechanisms may account for the unanticipated increase in disease flares in the atacicept MS clinical trials, 140 and suggest caution with dual BAFF/APRIL inhibition in other inflammatory diseases.…”
Section: Other Effec Ts Of Baff Inhib Iti On On Infl Ammationmentioning
confidence: 99%
“…In this context, a protective effect of BAFF inhibition on adiposity and insulin resistance may also be relevant. 144,145 Finally, multiple mouse studies have demonstrated decreased renal inflammation in BAFF-deficient and BAFF-R-Ig/TACI-Igtreated lupus models in excess of impacts on serum autoantibody titers. In the NZB/W model, our studies have shown protection from progressive lupus nephritis that could not be explained by a reduction in the autoantibody levels or reduced glomerular immune complex formation.…”
Section: Other Effec Ts Of Baff Inhib Iti On On Infl Ammationmentioning
confidence: 99%
“…In NOD mice, agents effecting timed depletion of B cells prevent diabetes [ 7 11 ] and reverse disease after onset [ 7 , 8 , 12 ]. These include anti-human CD20 antibody in human CD20 (hCD20)/NOD transgenic mice (in which the human gene MS4A1 , encoding hCD20, is expressed), anti-mouse CD20 antibody, anti-CD22 antibody coupled to immunotoxin, B-Lys/BAFF neutralisation and BCMA-Fc chimerised protein [ 7 , 8 , 12 ].…”
Section: Introductionmentioning
confidence: 99%